SARS-CoV-2 antibody response after BBIBP-CorV (Sinopharm) vaccination in cancer patients: A case-control study - Safarnezhad Tameshkel, Fahimeh; Abedin Dargoush, Shabnam; Amirkalali, Bahareh; Javadi, Saeedeh; Ghiaseddin, Ali; Alimohamadi, Yousef; Basi, Ali; Jamshidi Makiani, Mahin; Zamani, Farhad; Karbalaie Niya, Mohammad Hadi (Frontiers in Medicine, 2023)
Background Long-term safety and efficacy of BBIBP-CorV vaccine especially in individuals with chronic diseases, like cancer, is under investigation. In the present prospective study, we aimed to evaluate severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) antibody response with BBIBP-CorV vaccine in Iranian cancer patients. Methods All the patients registered to receive BBIBP-CorV (Sinopharm) vaccine were divided into two groups of with (cases = 107) and without (controls = 45) history of cancer. Serum levels of SARS-CoV anti-spike recombinant receptor binding domain (anti-sRBD) and anti-nucleocapsid (anti-N) IgG serum levels were measured on days 0 (phase 0), 28–32 (phase I), and 56–64 (phase II) of vaccination. The data were analyzed using SPSS, version 22. Results Totally, 152 individuals (67.1% females) with the mean age of 46.71 ± 15.36 years were included. Solid cancers included 87.8% of the cancer cases (46.7% gynecological and 31.8% gastrointestinal cancer). At Phases I and II, positive anti-sRBD IgG and anti-N IgG were significantly lower among the cases in total analysis. Side effects were not significantly different between the cases and controls. The lowest positive anti-sRBD IgG test was observed among the cancer patients who were simultaneously receiving chemotherapy (35.3%). Anti-sRBD IgG and anti-N IgG serum levels significantly increased at phases I and II in total analysis and in each group. In addition, serum anti-sRBD IgG increased during the three phases and it was significantly higher in the control group. Conclusion Full vaccination of COVID-19 by BBIBP-CorV in immunocompromised patients such as cancer patients is safe and effective and could induce antibody response but in lower levels compared to healthy people. Probable causes to have minor antibody response found in males, older ages, individuals with BMI ≥ 25, those without past history of COVID-19 and with hematologic cancers. No significant side effects after vaccination were seen.